Tectonic Evolution of a part of the English River Subprovince, Northwestern Ontario - Westerman, John Christopher (My University, 1978)
The English River Subprovince of Northwestern Ontario is an Archean gneissic terrain flanked by the greenstone-granite terrains of the Uchi and Wabigoon Subprovinces. Detailed and regional investigations have unravelled the complex question of the relative ages of rocks within these subprovinces.
Three tectonic rock assemblages have been defined. Tectonic assemblage I occupies the southern and central parts of the English River Subprovince and forms part of the English River Plutonic complex. This assemblage is dominated by severely deformed granitoid gneisses containing isoclinal D1 folds within the gneissic banding which are hence considered to be the oldest rock unit present (Cedar Lake gneisses).
Amphibolitic enclaves within the gneisses may represent an early supracrustal assemblage or a dyke swarm intruded into the gneisses. A subsequent tectonic event (D2) has produced isoclinal folds in both gneissic banding and amphibolite enclaves.
Strongly foliated tonalites and granodiorites of the Clay Lake Granitoid suite do not contain isoclinal (D2) folds and appear to have intruded the Cedar Lake gneisses and their associated amphibolites. This cannot be demonstrated unequivocably however due to later deformation and the Clay Lake Granitoid Suite is hence included in Tectonic assemblage I.
Tectonic assemblage II underlies the northern part of the English River Subprovince and forms part of the English River Metasedimentary Migmatite Complex. The assemblage is dominated by garnet and cordierite bearing metasedimentary gneisses with a high proportion of granitoid leucosome. Metavolcanic rocks are restricted to a narrow belt at the southern margin of the complex.
It has been demonstrated elsewhere that rocks of tectonic assemblage II may be traced laterally into metasediments and metavolcanic rocks of the Uchi Subprovince with which they are partly coeval. A metaconglomerate at Perrault Lake contains clasts of foliated tonalite similar to rocks of the Clay Lake Granitoid Suite. Rocks of tectonic assemblage II have never been found as inclusions within rocks of tectonic assemblage I. This implies that tectonic assemblage II was deposited, at least in part, on a sialic basement of tectonic assemblage I.
The Twilight Gneisses of the Clay Lake area and pillow lavas and banded iron formation of the Cliff Lake area are correlated with rocks of Tectonic assemblage II. These rocks do not contain isoclinal (D2) folds but have been affected by a period of strong layer-normal compression (D3). The occurrence of Twilight gneisses in the cores of later domal structures, below rocks of tectonic assemblage I, indicates that the D3 event was associated with subhorizontal tectonics causing interleaving of "basement" and "cover".
The D3 deformation was the first event to affect rocks of tectonic assemblage II. It was accomplished by a high grade regional metamorphism producing upper amphibolite facies mineral assemblages over wide areas of the English River Subprovince. Granulitic mineral assemblage were produced in the Clay Lake area under conditions estimated to be in the range 650-750°C and 4.5 to 7.0 kb.
The D3 tectonic event was succeeded by intrusions of tectonic assemblage III which range from equigranular tonalites through porphyritic granodiorites to equigranular pink granites. These intrusions were emplaced throughout the English River Subprovince and are probably temporal equivalents of the "diapiric granitoid intrusions" of the Uchi and Wabigoon Subprovinces. The presence of both foliated and massive varieties of all compositions suggests that several phases of emplacement occurred. Trace element data suggests that the intrusive rocks were not generated from rocks compositionally similar to those of tectonic assemblage I.
Intrusion of tectonic assemblage III produced a variety of interfering minor structures in pre-existing rocks. Major dome and basin structures were produced in the Cedar-Clay Lakes area and the prevaling vertical attitude of pre-existing foliations was accomplished throughout the English River Subprovince at this time.
Major faulting at the southern boundary of the English River Subprovince appears to predate intrusions of tectonic assemblage III.
Keywords: Geology; Geology